Rietveld refinement, magnetic and dielectric properties of Sr2+-Co2+-doped Zn2Y-type hexaferrites - Ibrahim Mohammed; J. Mohammed; Tchouank Tekou Carol T; A.K. Srivastava (Hybrid Advances, 2023)
In this experimental study, Sr2+-Co2+ was doped in Zn2Y-type hexaferrite to improve its magnetic and dielectric properties. Sol-gel auto combustion was used to synthesize Ba2-xSrxZn2-yCoyFe12O22 (x ​= ​0.0, 0.4, 0.8 and y ​= ​0.0, 0.5, 1.0), and the Retrieved refinement of XRD data confirmed the single-phase Y-type. Lattice constants a and c decreased from 5.867 to 5.854 Å and 43.566 to 43.470 Å, respectively. FTIR identified the absorption bands of hexaferrite at 405 cm-1 and 546 ​cm−1. An average grain size from FESEM decreased from 350 to 250 ​nm. Saturation magnetization and coercivity from M-H hysteresis loop for x ​= ​0.0, y ​= ​0.0, x ​= ​0.4, y ​= ​0.5, and x ​= ​0.8, y ​= ​1.0 are 40.04 emu/g, 42.77emu/g, 52.91emu/g, and 381.24 ​Oe, 261.44 ​Oe, 236.14 ​Oe respectively. The decrease in grain size, coercivity, and an increase in saturation magnetization make the prepared sample suitable for application in magnetic recording media. The material also deemed ideal for microwave devices due to its decreased dielectric constant values